Altered levels of circulating cytokines and microRNAs in lean and obese individuals with prediabetes and type 2 diabetes. Issue 1 (21st November 2016) - Nunez Lopez, Yury O.; Garufi, Gabriella; Seyhan, Attila A.
Abstract : Today obesity and type 2 diabetes (T2D) have both reached epidemic proportions. Abstract : Today obesity and type 2 diabetes (T2D) have both reached epidemic proportions. However, our current understanding of the primary mechanisms leading to these diseases is still limited due to the complex multifactorial nature of the underlying phenomena. We hypothesize that the levels of specific cytokines and miRNAs vary across the diabetes spectrum and unique signatures associated with them may serve as early biomarkers of the disease and provide insights into respective pathogenetic mechanisms. In this study, we measured the circulating levels of cytokines and microRNAs (miRNAs) in lean and obese humans with prediabetes ( n = 21), T2D ( n = 17), and healthy controls ( n = 20) (ORIGINS trial, NCT02226640). Data were analyzed by fitting linear models adjusted for confounding variables (BMI, age, and gender in the diabetes context and age, gender, and diabetes status in the obesity context) and implementing nonparametric randomization-based tests for statistical inference. Group differences and correlations ( r > 0.3) between variables with P < 0.05 were considered significant. False discovery rates (FDR) correcting for multiple testing were calculated using the Benjamini–Hochberg correction. We found a number of circulating cytokines and miRNAs deregulated in subjects with obesity, prediabetes, and T2D. Specifically, cytokines IL-6, IL-8, IL-10, IL-12, and SFRP4, as well as miRNAs miR-21, miR-24.1, miR-27a, miR-28-3p, miR-29b, miR-30d, miR-34a, miR-93, miR-126, miR-146a, miR-148, miR-150, miR-155, and miR-223, significantly changed across the diabetes spectrum, and were associated with measures of pancreatic islet β cell function and glycemic control, among others. Notably, SFRP4 was the only studied cytokine that was significantly associated with obesity, prediabetes, and T2D, which underscores the important role of this molecule during disease development and progression. Our data suggest that changes in circulating miRNAs and cytokines may have clinical utility as biomarkers of prediabetes.